The longitudinal trends in the relationship between drug-induced extrapyramidal symptoms and personal and social performance in a population of the patients with schizophrenia: A latent growth model. (30th April 2016) - Park, In-Jo; Jung, Dong Chung; Hwang, Samuel Suk-Hyun; Jung, Hee Yeon; Yoon, Jin-Sang; Kim, Chul-Eung; Ahn, Yong Min; Kim, Yong Sik
Abstract: The aim of this study was to explore the longitudinal trends in the relationship between personal and social functioning and drug-induced extrapyramidal symptoms (DIEPS). The baseline sample included 484 patients with schizophrenia. Participants were assessed at baseline, weeks 4 (time 2), 8 (time 3), and 12 (time 4) regarding social functioning, and DIEPS. In latent growth analysis, the path coefficient between the intercept for the DIEPSS and the intercept for the PSP indicated a significant cross-sectional relationship between these two variables. And the path coefficient between the intercept of the DIEPSS and the slope of the PSP was also significant, indicating that patients who initially had more serious side effects tended to exhibit less improvement in their personal and social functioning over time. Similarly, a significant path coefficient between the slopes of the two variables indicated a dynamic and possibly reciprocal association over time. In addition, K-PSP scale showed good construct validity and reliability. Based on the standardized PSP scale, our results demonstrate DIEPSS induced by antipsychotic treatment dynamically affect personal and social functioning over time, a negative association between psychosocial aspects and the DIEPS. Highlights: We explored longitudinal trends in the relationship between PSP and DIEPS. Personal and social functioning was significantly negatively correlated with symptom severity. DIEPS dynamically affect personal and social functioning over time.